The added value of SPECT/CT in complicated osteomyelitis - Tag, Naima (Stellenbosch : Stellenbosch University, 2013)
ENGLISH ABSTRACT: Background: The detection of bone infection can be very difficult especially in bone with altered structure due to prior trauma or surgical procedures. Complicated osteomyelitis (COM) is becoming a public health problem especially with the difficult choice between, high cost surgery and prolonged courses of intravenous or oral antibiotic therapy, as well as the social and psychological effect of longterm disease and disability of the patient. The correct localisation of especially bone infection is still a challenge for the clinician. The single photon emission computed tomography/low dose computed tomography (SPECT/CT), by fusing the functional information with the anatomical parts, is a wellestablished tool used in many nuclear medicine studies. This improves the overall quality of the study with more clear answers. The aim of the study was to determine the added value of SPECT/CT in the management of complicated osteomyelitis (COM) in patients with endo-prosthesis, post traumatic osteomyelitis with and without metal implants and diabetic foot. Methods: This was a prospective study, between February 2010 and February 2012. Patients with suspected COM who fulfilled the selection and inclusion criteria were included. All had abnormal three phase bone scan followed by infection imaging with 99mTc labelled white blood cells and 99mTc -colloid if the99mTc labelled white blood cell study was abnormal. 67Ga citrate was used in vertebral involvement. Planar and SPECT/CT images were reviewed for presence of abnormal uptake and for its localization in bone and soft tissue. Scan results were defined as positive or negative. Both planar and SPECT/CT images were compared regarding diagnosis and precise localization of infection. The final diagnosis was obtained from surgical specimen or microbiological culture as well as clinical follow-up of all patients. Results: There were 72 patients, 29 male and 43 female with mean age of 57 yrs [range 27-88].There were 24 patients with prosthesis, 16 with hip prosthesis (PH=16), and 8 with knee prosthesis (PK=8). There were 44 patients with post traumatic osteomyelitis, 26 with metal implants (TOM=26) and 18 without metal implants (TOWM= 18). Four patients had diabetic foot (DF= 4). Infection was diagnosed in 19/72 patients on planar images and in 21/72 on SPECT/CT. Infection was diagnosed in 4 patients with prosthesis, 16 patients with post traumatic injury and one diabetic foot patient. The four patients with prosthesis, SPECT /CT added diagnostic value by excluding osteomyelitis in 3 patients and by defining the exact extent and localizing soft tissue and bone infection (STI/OM) in one patient. In 16 patients with post traumatic OM on planar images, SPECT /CT added diagnostic value, by excluding OM in 4 patients and confirming only STI, better localisation of the uptake in bone and soft tissue in 5 patients, of them 2 patient was negative on planar, and in 7 patients, confirmed and defined the exact extent of both OM and STI. One diabetic foot was positive for STI on the planar, the SPECT/CT added diagnostic value by defining the extent of the infection. In summary the added value of SPECT/CT was: a. Overall infection: 1. Exclusion of osteomyelitis by confirming only soft tissue involvement: 7 patients (10%) 2. Better localization in bone and soft tissue: 6 patients (8%) 3. Better delineation of extent of infection: 9 patients (12%) 4. None: 50 patients (70%) b. In positive cases only: 1. Exclusion of osteomyelitis by confirming only soft tissue involvement: 7 patients (33%) 2. Better localization in bone and soft tissue: 5 patients (24%) 3. Better delineation of extent of infection: 9 patients (43%) 4. None: 0 patients The overall sensitivity, specificity, positive predictive value, negative predictive value and accuracy for infection, on planar was 90%, 100%, 100%, 97%, 97%, respectively and for SPECT/CT 100%, 100%, 100%, 100%, 100%. For OM on planar, the sensitivity, specificity , positive predictive value, negative predictive value and accuracy was 100%, 89%, 53%, 100%, 90%, respectively and for SPECT/CT 100%, 100%, 100%, 100%, 100%. Conclusion: In complicated osteomyelitis, SPECT/CT is useful in localizing, defining the exact extent of infection where the planar images are abnormal, with no added value if the planar images are negative. We recommend in clinical practice the routine use of hybrid SPECT/CT imaging in complicated osteomyelitis when planar images are abnormal.